2004
DOI: 10.1007/s10624-004-3587-3
|View full text |Cite
|
Sign up to set email alerts
|

MTV, Technology, the Secular Trend, and HIV/AIDS: Why Kenyan Parents Need to Learn about Adolescent Development

Abstract: As technological innovation increases the pace of communication and trade, traditional patterns of family interaction, education for adult social and vocational roles, belief systems, health and dietary practices also change. This is so because it is generally the young who are most heavily exposed to imported ideas and practices. They become the early adopters not only of technology, but also of trivial fashion fads and of profound, life-changing behavior, values, and ideology. At no stage in life is this mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…The aforementioned literature shows that there are several programs in place to keep HIV/AIDS on the consciousness of Africans. The mass media in Kenya have targeted young sexually active people through media such as billboards to promote VCT (Ginsberg & Gekonge, 2004). Marum et al (2008) analyzed data from more than 130 VCT sites in Kenya and found that utilization of mass HIV testing services increased with the use of “professional, intensive mass media campaigns” (p. 2019).…”
Section: Kenya and Hiv/aids Media Strategiesmentioning
confidence: 99%
“…The aforementioned literature shows that there are several programs in place to keep HIV/AIDS on the consciousness of Africans. The mass media in Kenya have targeted young sexually active people through media such as billboards to promote VCT (Ginsberg & Gekonge, 2004). Marum et al (2008) analyzed data from more than 130 VCT sites in Kenya and found that utilization of mass HIV testing services increased with the use of “professional, intensive mass media campaigns” (p. 2019).…”
Section: Kenya and Hiv/aids Media Strategiesmentioning
confidence: 99%